Intelligent Survivor Detection System for Post-Earthquake Rescue Operations Using IoT and Sensor-Based Monitoring - Sarosh Aziz; Shahbaz Ali Khan; Abdul Salam Shah; Muhammad Adnan Kaim Khani; Adil Maqsood; Asadullah Shah (Journal of ICT, Design, Engineering and Technological Science, 2026)
The paper introduces a system to enhance living human detection in earthquake disaster scenarios. The focus is on developing an overall solution to quickly identify and locate each person trapped within damaged structures or in debris. The suggested system incorporates a Passive Infrared (PIR) sensor, an Ultrasonic sensor, and a Microwave sensor into a small gadget that can be mounted to a telescopic selfie stick to reach confined areas. The main goals will be to develop a device capable of real-time human presence detection, to provide a visual output as feedback to help rescue teams respond efficiently, and to include an alarm system that alerts rescue teams when trapped human beings are detected. The system’s methodology would use PIR sensors to detect heat and movement, Ultrasonic sensors to reflect sound waves, and Microwave technology to detect movement and identify any living human being behind the walls. An Arduino UNO microcontroller is used for data processing and control to ensure the system is practical. The sensors are strategically incorporated into a portable device for easy deployment at disaster-stricken locations. In general, the system will play an important role in enhancing response to earthquake disasters. The expected outcomes are the successful creation of a working prototype, faster response times to save trapped people, and an understanding of the limitations of the sensors in earthquake scenarios. The article describes the new application of technology to address severe problems in the event of an earthquake or other natural disaster, helping save human lives and enhancing disaster management programs.